2016
DOI: 10.1007/s13258-016-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress-induced changes of microRNAs in diploid and autotetraploid Paulownia tomentosa

Abstract: Drought stress adversely affects plant productivity. Growth and timber production of Paulownia trees are limited under drought stress. Changes in gene expression patterns and miRNA in different ploidy of Paulownia tomentosa have been investigated. However, the responses of P. tomentosa to drought stress at the microRNA (miRNA) level have not been reported so far. To identify miRNA candidates and their target genes involved in the drought stress response in diploid and tetraploid P. tomentosa, four small RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…While the broad advantages of historical or evolutionary autopolyploidy on environmental adaption are commonly recognized (Comai, 2005;Fasano et al, 2016;Parisod et al, 2010), the improved stress tolerance of neopolyploids and the underlying molecular mechanisms have not been explicitly investigated. With the advent of high throughput sequencing, differences in transcriptome and miRNAome profiles between diploids and polyploids in the presence of a given stressor are investigated (Allario et al, 2011;Cao et al, 2017;Fan et al, 2016;Liu and Sun, 2017;Stupar et al, 2007). These studies demonstrated that a limited number of the transcribed genes are differentially expressed, implying that polyploidization may cause subtle changes in the expression of specific genes responsible for stress tolerance (Allario et al, 2013;Tan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the broad advantages of historical or evolutionary autopolyploidy on environmental adaption are commonly recognized (Comai, 2005;Fasano et al, 2016;Parisod et al, 2010), the improved stress tolerance of neopolyploids and the underlying molecular mechanisms have not been explicitly investigated. With the advent of high throughput sequencing, differences in transcriptome and miRNAome profiles between diploids and polyploids in the presence of a given stressor are investigated (Allario et al, 2011;Cao et al, 2017;Fan et al, 2016;Liu and Sun, 2017;Stupar et al, 2007). These studies demonstrated that a limited number of the transcribed genes are differentially expressed, implying that polyploidization may cause subtle changes in the expression of specific genes responsible for stress tolerance (Allario et al, 2013;Tan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies proved that several pathways to response to salinity stress, and chromosomal abnormality flora used several processes to adapt to high salt concentration condition involving in cumulating Na + extrusion in root, rising Na + transport to leaf, regulating osmotic, enhancing the genes expression related to antioxidant, mitigating ROS, photosynthesize cues, changing SNP marker related to salt stress, up-regulating aquaporin genes, phytohormone transduction cues, protein processing, regulating transcription factors, up-regulating ATP synthase to enhance ion transport changing proton; and using miRNAs [55][56][57][58][59][60][61][62][63][64]. To adapt with water insufficiency, chromosomal abnormal plants through miRNAs mechanisms and target genes controlling transcriptional regulation, hormone metabolism and plant defense, a rise in ABA content cope with drought stress in several polyploidy plants were observed in several plant species such as Paulownia fortunei, Paulownia australis, P. tomentosa, Lycium ruthenicum [65][66][67][68][69][70]. Antioxidant defense systems were activated to support heat tolerance sufficiently in Dioscorea and Arabidopsis [71,72].…”
Section: Chromosomal Abnormality Enhances Abiotic and Biotic Tolerancementioning
confidence: 99%
“…Additionally, 356 candidate microRNAs were discovered by degradome analysis that target transcripts connected to transcriptional adjustment, phytohormone metabolism and plant protection. In detail, only in the higher ploidy plant under shortage of water were miR4 and miR156 induced [54]. In the octaploid tobacco plant (Nicotiana benthamiana) polysomic polyploid plants enhance cold stress by increasing antioxidant (SOD, CAT, APX...) compared to tetraploid [104].…”
Section: Polysomic Polyploid Can Enhance the Ability To Adapt To Abiomentioning
confidence: 99%
“…In trees, gene expression and transcriptomes found genes linked to biosynthesis, leading to change in transduction pathways and ethylene after polysomic polyploid resulting in morphological changes [51], as well as pivotal differential expression belong to carbon fixation group and energy metabolism group [52], photosynthesis, the synthesis of lignin, and the enhancement of manifested transcription factors in tetraploid supporting salt tolerance [53]. Transcriptomes in trees also revealed several miRNAs that play a role in drought stress [54] [55] [56]. Besides, shrubs showed divergent photosynthesis processes and the promotion of biosynthesis as well as adjusted phytohormone pathways including auxin, gibberellins, cytokinin, and ethylene [57], increased the proline content and expression of aquaporin genes [58].…”
mentioning
confidence: 99%